2022
DOI: 10.31219/osf.io/vgdbt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations of Air Pollution with Peripheral Inflammation and Cardiac Autonomic Physiology in Children

Abstract: Climate change-related disasters have drawn increased attention to the impact of air pollution on health. 122 children ages 9-11 years old (M(SD) = 9.91(.56)) participated. Levels of particulate matter (PM2.5) near participants’ homes were obtained from the Environmental Protection Agency. Cytokines were assayed from 100 child serum samples: IL-6, IL-8, IL-10, and TNFα. Autonomic physiology was indexed by pre-ejection period (PEP), respiratory sinus arrhythmia (RSA), cardiac autonomic regulation (CAR), and bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…Another potential mechanism by which caregiver social support may influence the infant gut microbiome is via reductions in caregiver psychological and physiological stress. A few studies have found that higher social support for caregivers is associated with lower perceived caregiver stress and lower rates of caregiver depression and anxiety in the postnatal period (Jahnke et al, 2021;Nelson et al, 2020), which may influence patterns of parenting behaviors and parent-child interactions (Beebe et al, 2011;Feldman et al, 2009;Granat et al, 2017;Lemus et al, 2022) with important influences on the development of biological systems implicated in the gut microbiome, including infant stress-response systems (Feldman et al, 2009;Parenteau et al, 2020). Additionally, some studies have found that maternal social support during pregnancy serves as a buffer against the physiological impacts of psychological distress (Giesbrecht et al, 2013), suggesting that another potential mechanism by which caregiver social support influences the infant gut microbiome is by preventing caregiver stress from "getting under the skin."…”
Section: Caregiver Social Support and The Gut Microbiomementioning
confidence: 99%
“…Another potential mechanism by which caregiver social support may influence the infant gut microbiome is via reductions in caregiver psychological and physiological stress. A few studies have found that higher social support for caregivers is associated with lower perceived caregiver stress and lower rates of caregiver depression and anxiety in the postnatal period (Jahnke et al, 2021;Nelson et al, 2020), which may influence patterns of parenting behaviors and parent-child interactions (Beebe et al, 2011;Feldman et al, 2009;Granat et al, 2017;Lemus et al, 2022) with important influences on the development of biological systems implicated in the gut microbiome, including infant stress-response systems (Feldman et al, 2009;Parenteau et al, 2020). Additionally, some studies have found that maternal social support during pregnancy serves as a buffer against the physiological impacts of psychological distress (Giesbrecht et al, 2013), suggesting that another potential mechanism by which caregiver social support influences the infant gut microbiome is by preventing caregiver stress from "getting under the skin."…”
Section: Caregiver Social Support and The Gut Microbiomementioning
confidence: 99%